Socioeconomic hardship and delayed reward discounting: Associations with working memory and emotional reactivity. (June 2019) - Oshri, Assaf; Hallowell, Emily; Liu, Sihong; MacKillop, James; Galvan, Adriana; Kogan, Steven M.; Sweet, Lawrence H.
Abstract: Prolonged exposure to socioeconomic hardship (SH) is associated with greater delayed reward discounting (DRD), a form of impulsive decision-making that reflects a reduced capacity to delay gratification and a significant correlate of diverse risk behaviors, but the neurobehavioral mechanisms linking SH and DRD are unknown. An emerging hypothesis suggests that cognitive and affective stress associated with poverty may tax neurocognitive functions, such as working memory (WM), and lead to impulsive DRD. Furthermore, research suggests that emotional reactivity (ER) is an important dispositional factor to consider in the link between executive functions and DRD. Thus, we longitudinally examined the indirect effect of SH on impulsive DRD via a network of brain regions associated with WM function in a sample of young adults, and whether that link was moderated by ER. Participants were 119 rural African Americans (aged 19–24 years) assessed behaviorally on four occasions, with fMRI at the last time point. Results showed that, among emerging adults with higher ER, SH severity was predictive of increased DRD via reduced response in brain regions activated during an n-back WM task. These findings reveal both the cognitive and affective mechanisms that underlie the relationship between SH and DRD.